Relationship lending and bank loan covenant violations. (13th March 2021) - Bo, Xu Chong; Li, Wenyi; Shi, Jing; Zheng, Yi; Zhou, Qing
Abstract: We examine the association between relationship lending and the likelihood of bank loan covenant violations. We find that relationship lending reduces the probability of ex‐post covenant violations. The length of the lending relationships has an inverted U‐shaped effect on the likelihood of covenant violations. The borrowers and lenders both benefit from relationship lending, but long‐term lending relationships weaken the borrower's bargaining power.